중국의 대북한 동맹안보딜레마 관리대미인식과 북한지정학의 재구성을 중심으로 - 李熙玉; Hee Ok Lee; 朴龍國; Long Guo Piao (중소연구, 2013)
이글은 강대국의 대약소국 동맹딜레마 관리모델을 활용해 제2차 북핵실험 이후 중국의 대북정책 조정을 대미관계 변화의 차원에서 분석했다. 특히 제1차 핵실험 시 연루의 위험을 느끼고 대북정책을 조정한 중국이 제2차 북한 핵실험 이후에 왜 그 정책을 변화시켰는가를 주목하고 있다. 왜냐하면 제2차 북핵실험의 성격이 제1차 실험과 크게 다르지 않고 북·중 간, 중·미 간 양자관계가 이 국면에 영향을 미치지 않은 상태에서 변했기 때문이다. 이 글은 이러한 변화를 중?미관계의 인식과 정책, 그리고 이에 따른 북한의 지정학적 가치에 대한 재 주목에서 찾았다. 그 결정적인 계기는 2008년 미국발 금융위기였다. 이를 통해 중국은 미국의 세계전략은 물론이고 미국에 대한 근본적인 인식이 변화했다. 과거 미국에 대한 수동적 조정(accommodation)에서 보다 사안에 따라서 대립하면서도 협력하는 능동적 인식과 정책을 수행했다. 이 과정에서 북한에 대한 연루의 위험이 낮아지고 북한의 지정학적 가치를 고려한 북·중 관계와 이에 따른 새로운 대미전략이 부상했다. 더구나 중국은 북한의 제1차 핵실험 이후 대북정책에서 ``영향력의 딜레마``를 학습했기 때문에 새로운 대북 포용정책을 통해 북한을 관리하고자 했다. 동시에 북한도 중국의 대미균형이 자국의 안보부담을 덜어줄 수 있다고 인식한 동시에 중국을 결박(tethering)하여 대외관계에서 전략적 균형을 찾고자 했다. 이러한 동북아 국제관계는 상황적이라기보다는 중·미 관계의 변화라는 맥락 속에서 작동하고 있기 때문에 현재의 북·중 관계도 부분적인 조정에도 불구하고 유지될 가능성이 높다고 전망했다. The purpose of this paper is to examine the revision of China`s policy towards North Korea after North Korea`s second nuclear test from the perspective of the changing China-US relations. For this purpose, great power`s management of alliance dilemma with small power model is employed. Specifically, this paper analyses why China, after understanding the risk of entrapment, adjusted its policy towards North Korea at the time when North Korea conducted its first nuclear test, whereas it changed that policy at the North Korea`s second nuclear test. The reason for this is that the change happened in a situation where the nature of North Korea`s both nuclear tests was not significantly different, and also China-North Korea relations and China-US relations did not affected the conditions. From this prospective, this paper pays more attention to the perception and policy of China-US relations and the accompanying geopolitical value of North Korea. The 2008 financial crisis which was originated from the US was the crucial movement for this. After this crisis, China has changed not only its perspective about US`s global strategy, but also the fundamental perception about the US. Unlike the previous strategy in which China played a passive accommodation policy towards the US, it has now adopted an active perspective to cooperate with the US even in situation where conflicts prevail between the two. In this process, the risk of entrapment about the North Korea reduces, and a new relationship between North Korea and China which considers the geopolitical value of North Korea and China`s new strategy towards the US are emerging. Moreover, because China has learned ``the Dilemma of Influence`` from its experience in dealing with North Korea`s first nuclear test, it intends to deal North Korea through new engagement policy. At the same time, North Korea also intends to recognize that China`s balancing strategy towards the US can reduce its security burden, and that to match the strategic balancing in foreign relation with tethering China. In this way, international order of Northeast Asia are not situational;rather it is driven by the changing China-US relations. Therefore there is a high probability that the current North Korea-China relations will also continue. We can understand China`s new series of offensive dialogue by considering this structural change.